Characterised existing sweetpotato seed system actors, identified efficient seed distribution channels and market preferred varieties in Bukombe and Butiama districts, Tanzania - Rajendran, S.; Ochenje, I.; Ogero, K.; McEwan, M.; Wanjohi, L.; Mafuru, J.; Mussa, H.; Motts, N. (International Potato Center, 2021)
Tanzania is a major sweetpotato producer in sub-Saharan Africa. The area under sweetpotato has been rising steadily relative to main food staples. However, the yields have stagnated at around 4 t/ha compared with the potential yield of above 20 t/ha, partly due to limited access to quality seeds. Most farmers in SSA recycle seed from the previous crop or source from neighbours. This increases the probability of accumulating viruses, which may reduce the sweetpotato yield by over 50%. Studies have shown that farmers are willing to pay a premium for quality seeds. Therefore, an efficient seed distribution channel that ensures seeds move from the breeding stage to the multiplication stage without any disconnections between the nodes can provide farmers with better access to quality seed at an affordable price. However, there are disconnections in the current seed distribution channels, particularly between the public and private sectors. In addition, most farmers do not often replenish planting materials once they buy quality planting materials. There are hardly any exclusive seed multipliers in the seed value chain due to a lack of understanding about potential business opportunities. Identifying a sustainable and profitable business model for seed multipliers is important in ensuring that farmers are constantly supplied with quality planting materials when they need them. This needs greater efforts to demonstrate the benefits of using quality planting materials, establish delivery seed distribution channels to reach a large number of end-users, and strengthen farmer seed management capacities and farmer seed networks. A study was conducted in Mara and Geita regions to identify market preferred and the main sources of the sweetpotato roots. The survey on the root producers were carried to understand the acquisition and provision of the market-preferred varieties and the connections between the nodes in the existing seed distribution channels. The study also conducted key informant interviews with other key stakeholders such as the public sector (i.e., Tanzania Agricultural Research Institute-TARI). The team will propose a sustainable business model that can link formal and informal seed sectors for consistent supply of quality and market preferred planting materials to root producers. The study utilized “the structure, conduct, and performance (SCP)” tool to establish relationships in the sweetpotato seed market. The SCP paradigm postulates a causal relationship where the structure influences the conduct, and in turn, the conduct influences the performance. The structure refers to the type of market, pricing strategy, the degree of concentration of buyers and sellers, the level of product differentiation, and condition of entry in the market. The conduct is the behavior of buyers and sellers and how they react to each other strategy. The performance of the seed market considers indicators such as profit of the seed and root producers and seed security indicators. The study also mapped the linkages of the existing nodes of sweetpotato seed channels by looking at the seed acquisition and provision transactions. A total of 45 traders participated in the survey in Bukombe, Butiama, Ilemela and Nyamagana districts. Most of the traders were male, and the average age was between 37- 44 years in the four districts. Most traders are members of trader’s associations, some traders were in cooperatives, and a few were in digital platforms. The traders benefited from the association through access to credit, access to market information, facilitating joint marketing, and saving cash. The markets were mainly rural (Bukombe and Butiama) and urban markets (Ilemela and Nyamagana). The type of traders in these markets were either wholesalers or middlemen (aggregators), with most markets operating the whole day, where the contract between sellers and buyers is largely oral. The high season when the supply of sweetpotato roots is high in the market ran from February to June, while the low season runs from July to November. Overall, Polista (62%), Mage (40%), and Ukimwi (28%) were the three most traded in the market, but there were district differentials in the traded varieties. For instance, Ukerewe (56%) was the most traded variety in Butiama. The common attributes liked about these varieties include high dry matter, big root size, good taste for Polista, high dry matter, good color and high market demand for Ukimwi, long shelf life, high market demand, and good color of the flesh for Mage. The three most disliked attributes in Polista were late maturing, short storage life, and susceptibility to pests and diseases. In Ukimwi susceptible to pests and diseases, limited supply of planting material, and small size of the root. Low dry matter, late maturing, and high-water content were the three most disliked attributes of Mage variety. In the root and seed producers survey, a total of 110 households from the Bukombe and Butiama district participated in the rapid seed system assessment survey after being identified as a major source to sweetpotato markets in the region. The proportion of root producers who also produced seeds was higher in Bukombe (72%) than Butiama (42%), where the majority of the seed producers were not trained. Most producers produce seeds for their own use. However, the neighbor farmers play a dominant role in both seed acquisition and seed provision. The existing root buyers include wholesalers, commission agents/aggregators, retailers, and NGOs. Most farmers sell the roots to wholesale traders, followed by commission agents and retailers. The median size for sweetpotato root plots was 0.8 hectares in both districts, while the average size for sweetpotato seed plots was 0.2 hectares in Bukombe and 0.32 hectares in Butiama. The average root yield was 2,461 kg/acre in Bukombe and 2060kg/acre in Butiama. The average seed yield was 5,695kg/acre in Bukombe and 3,140 kg/acre in Butiama. Overall, the three most preferred varieties are Polista, Ukimwi, and Mage, but varied with the district. Polista variety was liked because of its high dry matter content, better taste, and high market demand. The traits that farmers disliked include matures late, has low yield and is not resistant to SPW. Ukimwi was preferred because it matures early, has high market demand, high dry matter. The traits producers disliked were less resistant to SPVD, not stress-tolerant, short shelf life, and limited access to planting material. The preferred attributes in Mage include high market demand, good flesh color, early maturing, and high root yield. However, the variety is late maturing, has low dry matter content, has a shorter shelf life, and less resistant to stress (drought and poor soils). About 90% of producers sell/share sweetpotato roots. The roots are mostly sold to wholesale traders, followed by commission agents, retailers, and NGOs. The average quantity sold by the respondents in the last year was about 8924 kg in Bukombe and 4850kg in Butiama. Only 26% and 53% of respondents sold seeds in Butiama and Bukombe, respectively. The most common varieties provided were Ukimwi (33%), Pisi tatu (27%), Uso wa mchina (20%) in Bukombe. Polista (57%) and Ukerewe (29%) were the most common varieties in Butiama. Farmers predominantly sold to sweetpotato producers in both Butiama (86%) and Bukombe (97%). Other seed buyers were international organizations, and local NGOs. Respondents sold to producers mainly because they were friends and relatives without expectations but sold to local NGOs, international organizations because they give higher prices. About 47% in Bukombe and 28% Butiama acquired seed from elsewhere. Ukimwi was the most dominant variety in Bukombe, while most respondents in Butiama received Polista and Ukerewe. At least half of the respondents chose these varieties because they were market preferred. The seeds were mainly sourced from sweetpotato producers because of close relationships (relatives and friends). TARI produced Kabode, Kakamega, NASPOT 12, and Mataya varieties through rapid multiplication in screen houses and conventional methods in open field plots. The three most preferred varieties were Kabode, NASPOT 12, and Mataya. All of them are early maturing, high yielding, with better nutritional benefits. Kabode and NASPOT 12 are also tolerant to SPVD and SPW. TARI has regular contact with about 20 decentralized vine multipliers and 30 farmers. In the last one year, TARI provided 5 types of varieties The five types of varieties that TARI provided were Kabode, Kakamega, NASPOT 12, Mataya, and Ejumula, where the seed class was basic. TARI provided a total of 1257 bundles to local NGOs in February at TSH 2500 for each bundle of 100 cuttings of 30cm size.